Effect of temperature on morphology and wear of a Cu-Ti-TiC MMC sintered by abnormal glow discharge - Cristian D Bohórquez; Sandra P Pérez; Armando Sarmiento; Martin E Mendoza (Materials Research Express, 2020)
Microstructure and tribological properties had been studied in a Cu-Ti-1%TiC MMC with titanium concentration of 10%, 15%, and 20%. The composite was manufactured following the pulvimetallurgical route that included: mechanical and ultrasonic mixing in 2-propanol, compaction at 400 MPa and sintering assisted by abnormal glow discharge in an atmosphere of 10% nitrogen and 90% argon. The discharge was established in the direct current regime and the voltage values were adjusted according to the sintering temperatures of 750 °C and 850 °C. The sintering process was carried out for 30 min and then cooled in the same atmosphere. As a result, a differentiated in morphology and wear properties were obtained in the sintered parts. At 750 °C a microstructure characterized by the stability of Ti grains with intermetallic precipitates such as CuTi _2 and CuTi were observed at the interface with the matrix. On the other hand, the intermetallic phases as Cu _3 Ti, Cu _4 Ti and CuTi _2 had been detected in the sintered at 850 °C. These phases were related to diffusive processes that occurred during the sintering, enhanced by the energy provided by the process. It had been observed that with increase of titanium content an improvement of the MMC tribological properties. In titanium contents of 20% at 750 °C was estimated a wear coefficient of 2.7 × 10 ^−8 mm ^3 .N ^−1 .m ^−1 with a track width of 312 μ m. Despite the pores originated during the sintering of MMC at 850 °C was found a wear coefficient value of 2.4 × 10 ^−8 mm ^3 .N ^−1 .m ^−1 and a track size of 778 μ m, related to the plastic deformation exerted on the porous structures during the wear process. Results of the tribological analysis lead that this compound may be applied in fields where the balance between adequate tribological properties and lightness are highly required such as the automotive, aeronautical and biomedical industries.